2003
DOI: 10.1096/fj.02-0841fje
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress‐related increase in ubiquitination in early coronary atherogenesis

Abstract: The ubiquitin‐proteasome system (UPS) is involved in the removal of damaged proteins and the activation of transcription factors, such as nuclear‐factor‐κB. Recent reports, however, questioned the functional activity of the UPS under conditions of increased oxidative stress, such as experimental hypercholesterolemia, which was the objective of our study. Pigs were placed on a normal chow diet (N) or on a hypercholesterolemic diet without (HC) or with vitamin C and E supplementation (HC+VIT) for 12 weeks. Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 43 publications
1
40
2
Order By: Relevance
“…Indeed, we showed previously that diet-induced HC (a surrogate of early atherosclerosis) led to renal functional and structural impairment, likely through activation of redox-sensitive mechanisms (3,4,19) that also involved the activation of the UPS (15,16). Furthermore, we also showed that the UPS is functionally active in early coronary atherogenesis (30). However, whether the UPS played any role in renal compromise in the early stage of atherosclerosis remained to be explored.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, we showed previously that diet-induced HC (a surrogate of early atherosclerosis) led to renal functional and structural impairment, likely through activation of redox-sensitive mechanisms (3,4,19) that also involved the activation of the UPS (15,16). Furthermore, we also showed that the UPS is functionally active in early coronary atherogenesis (30). However, whether the UPS played any role in renal compromise in the early stage of atherosclerosis remained to be explored.…”
Section: Discussionmentioning
confidence: 91%
“…We showed previously in both human (29) and animal (15,16,30) studies that activation of the UPS may potentially play a deleterious role in different stages of atherosclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…22 Various cellular stimuli, such as oxidative stress, induce ubiquitination of phosphorylated IkBs and subsequent degradation by the proteasome. 23 Degradation of IkBs results in unmasking of the nuclear localization signal of NF-B dimers, which subsequently translocates to the nucleus, where it induces the transcription of proinflammatory cytokines like TNF-␣ that play a central role in plaque instability progression. 24 In line with this construct, our findings also suggest that HRT may reduce phosphorylation and degradation of IkBs via the suppression of ubiquitin-proteasome activity, thus reducing NF-B activation.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Implications for the proteasome-sensitivity in vascular cells is an important consideration for clinical applications since the ubiquitin-proteasome system remains active in diseased blood vessels. [15][16][17] Alternate strategies to improve endothelial cell transduction by AAV have been actively sought. 18 These include AAV-2 retargeting using vascular cell-selective peptides 11,19,20 or the use of alternate serotypes.…”
mentioning
confidence: 99%